2018
DOI: 10.5430/ijhe.v7n4p99
|View full text |Cite
|
Sign up to set email alerts
|

Student Produced Videos - An Innovative and Creative Approach to Assessment

Abstract: The ability to think critically and creatively are essential graduate attributes for science students yet many science graduates lack these skills and may struggle to gain employment. As undergraduate science educators, we are aiming to improve critical thinking, creativity and the promotion of deeper learning in our students. We have designed and implemented an innovative and creative approach to assessment to engage students with laboratory practicals, which are a core component of the biomedical sciences at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…However, other studies illustrate how video can be used to capture cognitiveprocedural outcomes when students are tasked with documenting their completion of some experiment or exercise in the video rather than simply answering reflection questions (Erdmann & March, 2014;Speed, Lucarelli & Macaulay, 2018;Tierney, Bodek, Fredricks, Dudkin & Kistler, 2014). Speed et al (2018) asked biochemistry students to film video reports about experiments, with evidence of creative and critical thinking in videos and higher grades when compared with written lab reports. Tierney et al (2014) asked organic chemistry students to record themselves using a molecular model kit in response to prompted exercises with videos posted on VoiceThread.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, other studies illustrate how video can be used to capture cognitiveprocedural outcomes when students are tasked with documenting their completion of some experiment or exercise in the video rather than simply answering reflection questions (Erdmann & March, 2014;Speed, Lucarelli & Macaulay, 2018;Tierney, Bodek, Fredricks, Dudkin & Kistler, 2014). Speed et al (2018) asked biochemistry students to film video reports about experiments, with evidence of creative and critical thinking in videos and higher grades when compared with written lab reports. Tierney et al (2014) asked organic chemistry students to record themselves using a molecular model kit in response to prompted exercises with videos posted on VoiceThread.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has not informed the initiative and intentionality outcome; however, it would be helpful to know if the public video platform open to wider scrutiny encourages or discourages students from being honest and descriptive of their design process and from expressing vulnerability in describing any challenges or setbacks in design. Finally, with regard to the informal outcome engagement, a few studies have hinted that video assessment may be more engaging to students (Speed et al, 2018;Tierney et al, 2014). Speed et al (2018) reported that filming video reports was more engaging and enjoyable than writing reports.…”
Section: Q7mentioning
confidence: 99%
See 2 more Smart Citations
“…[Rifkin et al, 2010]. Though evidence exists supporting the use of science communication activities and mobile-filmmaking as ways to engage students, it is mainly based in tertiary courses [Clarkson et al, 2018;Speed, Lucarelli and Macaulay, 2018], where it is too late for students who opted-out from science years earlier.…”
Section: Introductionmentioning
confidence: 99%